Photoreceptor deactivation and retinal degeneration mediated by a photoreceptor-specific protein kinase C. - Smith, D.P.; Ranganathan, R.; Hardy, R.W.; Marx, J.; Tsuchida, T.; Zuker, C.S. (Science, 1991)
The protein kinase C (PKC) family of serine-threonine kinases has been implicated in the regulation of a variety of signaling cascades. One member of this family, eye-PKC, is expressed exclusively in the Drosophila visual system. The inaC (inactivation-no-afterpotential C) locus was shown to be the structural gene for eye-PKC. Analysis of the light response from inaC mutants showed that this kinase is required for the deactivation and rapid desensitization of the visual cascade. Light adaptation was also defective in inaC mutant flies. In flies carrying the retinal degeneration mutation rdgB, absence of eye-PKC suppressed photoreceptor cell degeneration. These results indicate that eye-PKC functions in the light-dependent regulation of the phototransduction cascade in Drosophila.